Sex Ratios, Divorce Laws and the Marriage Market - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2010)
We show how an interaction between the skewness of the sex ratio and the jump in divorce rates after a liberalization in divorce laws can obtain in a model of marriage market matching with non-transferable utility. This model is partly motivated by a significant cross-country correlation between these two variables. We also find that men’s hopes or fears about women’s marriage market odds are self-confirming under mutual consent, resulting in multiple equilibria. The multiplicity vanishes with a more skewed sex ratio or a liberalization of divorce laws. Our work sheds some light on the possible implications of divorce liberalization and pro-marriage policies.